Pengaruh Penggunaan Sosial Media Instagram Dimasyarakat Kampung Kandaga - Sandi Gustiandi; Tedi Kurniadi; Ahmad Rianda Lubis; Neng Aas Fauziah Rohmah (IHSA Institute, 2022)
Path occupies the fourth position with the dominance of users ranging in age from 20 to 25 years. We will conduct research in the form of a survey. The survey is a quantitative basic form